2006
DOI: 10.1381/096089206775565195
|View full text |Cite
|
Sign up to set email alerts
|

Intracolonic Penetration of the Laparoscopic Adjustable Gastric Banding Tube

Abstract: The laparoscopic adjustable gastric band (LAGB) has become a common, usually successful treatment for morbid obesity. Complications occur in 10-20%, most commonly band slippage and port system problems, especially infection of the port area. A rare complication is penetration of the band into the stomach. We report the penetration of the tube connecting the port system with the gastric band, into the colon 1 year after treatment of a port infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 14 publications
2
34
0
1
Order By: Relevance
“…Zappa described the same complication where the tubing was wrapped around a jejunal loop leading to intermittent obstruction [20]. There are two reports about an intracolonic migration of the tubing [21,22]. Migration was inflicted by previous treatment of a port infection, as was the case with our patient.…”
Section: Discussionsupporting
confidence: 63%
“…Zappa described the same complication where the tubing was wrapped around a jejunal loop leading to intermittent obstruction [20]. There are two reports about an intracolonic migration of the tubing [21,22]. Migration was inflicted by previous treatment of a port infection, as was the case with our patient.…”
Section: Discussionsupporting
confidence: 63%
“…Zengin et al [13] reported a case of disconnection of the tubing from the subcutaneous port with subsequent erosion into the jejunal wall in a 36-year-old man post LAGB. Hartmann et al [14] reported colonic perforation by the connecting tube. Zappa et al [7] documented recurrent jejunal obstruction and volvulus caused by the connecting tubing 3 years following LAGB.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these patients underwent investigation for pelvic inflammatory disease, gynecological problems, renal colic, or acute appendicitis. Small-bowel obstruction and migration into jejunal and colonic walls caused by the connecting tube were reported in patients with prolonged abdominal pain [8][9][10][11]. Ability for free food passage and weight gain are other clinical signs of tube disconnection.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of tube disconnection from access port was reported in 0.45-24% of patients [3][4][5][6][7]. Intractable abdominal pain, small-bowel obstruction, and migration of the tube into jejunal and colonic walls were described as complications of connecting tube disconnection [8][9][10][11]. Early diagnosis and treatment of port disconnection can prevent some of these complications.…”
mentioning
confidence: 99%